Simultaneous Detection and Quantification of Three Novel Prescription Drugs of Abuse (Suvorexant, Lorcaserin and Brivaracetam) in Human Plasma by UPLC–MS-MS. Issue 3 (6th October 2018) - Iqbal, Muzaffar; Khalil, Nasr Y; Ezzeldin, Essam; Al-Rashood, Khalid A
Abstract: Suvorexant (SVR), lorcaserin (LCR) and brivaracetam (BVR) have been recently approved for the treatment of insomnia, obesity and epilepsy, respectively. Despite their clinical uses, these drugs have some abuse potential and have been enlisted under the schedule IV (SVR, LVR) and schedule V (BVR) categories of the Controlled Substances Act. A sensitive UPLC–MS-MS assay was developed for simultaneously determining SVR, LCR and BVR in human plasma. The liquid–liquid extraction method, using tert-butyl methyl ether as an extracting solvent, was used for sample preparation. Chromatographic separation was performed by using the Acquity BEH C18 column, using 10 mM ammonium acetate/acetonitrile/formic acid (15/85/0.1%; v / v / v ) as the mobile phase. For sample ionization, electrospray ionization was used in the positive-ion mode. The multiple-reaction monitoring mode was used for detecting and quantifying analytes by using separate precursor-to-product ion transitions. The assay was validated following the SWGTOX guidelines, and all validation results were within the acceptable limits. The calibration curves of the analytes in the plasma were found to be linear, and the coefficient of determination ( R 2 ) was ≥ 0.992 for all the three analytes. The limit of detection values for SVR, LCR and BVR were 0.08, 0.11 and 0.26 ng/mL, respectively, whereas the limit of quantification values were 0.16, 0.27 and 0.65 ng/mL, respectively. The assay developed in this study is suitable for the identification and quantification of SVR, LCR and BVR in the forensic laboratory.